Serum Sodium Level in Children Suffering from Acute Bronchiolitis Admitted in a Tertiary Care Hospital (Bangladesh Journal of Child Health, 2019)
Background: Acute bronchiolitis is a clinical syndrome produced by inflammation of the terminal bronchioles. It usually occurs in association with viral respiratory tract infection. Children with bronchiolitis are at risk of developing hyponatraemia. The objective of this study is to find out any change of serum Na+ values in bronchiolitis.Methodology: A cross sectional observational study was done during January to June 2015 among the children between age of 2 months to 2 years admitted in the pediatric ward of Institute of Child Health & Shishu Sasthya Foundation Hospital, Dhaka, who were diagnosed as acute bronchiolitis. Data were collected by interviewing, physical examination and laboratory investigations and recorded through a proforma. Data were processed and analyzed using computer software SPSS.Results: A total of 50 cases suffering from bronchiolitis were studied. Among them only 5 (10.0%) cases had hyponatraemia considered as group I and rest 45 (90.0%) patients had normonatraemia considered as group II. The mean age was found to be 10.8±5.3 months and 8.91±5.8 months in group I and group II respectively. Male was found 4 (80.0%) in group I and 27(60.0%) in group II. Mean respiratory rate was found to be 50.0±1.4 per min in group I and 54.18±3.9 per min in group II, which was significantly higher in normonatraemia group. Seizure, requirement for mechanical ventilation and mortality were not found in any child suffering from acute bronchiolitis.Conclusion: These results indicate that normonatraemia was predominant and hyponatraemia was found only 10% cases and all were in mild degree. The clinical outcome of all the hyponatraemia cases was good and they were not associated with any complications.Bangladesh J Child Health 2018; VOL 42 (3) :4-8